A novel methodology for designing sustainable cement mortars with quartzite dust, gypsum, and sewage sludge ash: enhanced mechanical performance, fire resistance, and CO2 reduction - Abdessalam Guedri; Naji Guedri; Oscar Baeza-Urrea; Jean-Frank Wagner (Euro-Mediterranean Journal for Environmental Integration, 2026)
This study investigates the development of cementitious mortars with enhanced mechanical and physical properties compared to the reference cement paste (S01), while simultaneously reducing cement content, minimizing variability (lower coefficient of variation, CV), and decreasing CO₂ emissions. Thirteen mortar formulations were prepared according to an experimental design in which Ordinary Portland Cement (OPC) was partially replaced with different additives (ADD): thermally treated industrial waste (sewage sludge ash, SSA) and mineral-based materials (sand, S; quartzite dust, QD; and natural Tunisian gypsum, GPS), with ADD/OPC ratios ranging from 0.20 to 0.62. The physico-mechanical properties and fire resistance of the most promising formulations were evaluated. Results indicate that cement content could be reduced by up to 27%, leading to an estimated CO₂ reduction of 243 kg per ton of OPC, while achieving significant improvements in compressive strength (+ 21.97%, CV = 4.54%) and flexural strength (+ 58.72%, CV = 3.37%) in QD-containing mortars, accompanied by increased density and toughness. GPS and SSA contributed to increased lightness and porosity due to their low bulk density and porous microstructure, as confirmed by SEM analysis. Based on these findings, S3 GPS and S3 QD were identified as the most promising and environmentally sustainable formulations for fire resistance tests, with S3 QD mortars exhibiting an 18% higher thermal resistance than S3 GPS .